Evaluation of Antituberculosis Potential of N-Hexane Extract And Ethanol Extract of Soursop Leaves (Annona Muricata L.) In Vitro - Muhammad Sulaiman; Cut Fatimah; Muhammad Gunawan; Safrina Safrina (LPPM Universitas Abdurrab, 2024)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis, primarily affecting the lungs and transmitted through droplets. Indonesia ranks second in the world for pulmonary TB cases. Due to increasing resistance to synthetic TB drugs, alternative treatments are needed, such as soursop leaves, which are known to treat symptoms like coughing and bleeding. This study aims to evaluate the potential of soursop leaf extract against TB. The method used in this study is the Lowenstein-Jensen method with varying concentrations. Sputum samples from TB-positive patients were identified using Zheil-Nelsen staining, while soursop leaf extract was obtained through percolation using n-hexane and ethanol fractions. The results showed that the moisture content of soursop leaf powder was 5%, meeting the simplisia standard. The antituberculosis test revealed resistance to synthetic drugs starting from the second week, while the n-hexane extract showed resistance from the first week. The ethanol fraction inhibited bacterial growth until the third week, but positive growth occurred in the fourth week. Therefore, soursop leaf extract, particularly the ethanol fraction, shows potential as an alternative TB treatment, which warrants further investigation.